Gene Expression Profile Reveals a Prognostic Signature of Non–MSI-H/pMMR Colorectal Cancer - Liu, Zaoqu; Xu, Hui; Ge, Xiaoyong; Weng, Siyuan; Dang, Qin; Han, Xinwei (Frontiers in Cell and Developmental Biology, 2022)
Studies have demonstrated that non-MSI-H/pMMR colorectal cancer (CRC) has a worse prognosis and relapse rate than MSI-H/dMMR CRC. Hence, searching for a novel tool to advance the prognostic management of non-MSI-H/pMMR CRC is vital. In this study, using three independent public cohorts and a clinical in-house cohort, we developed and validated a microsatellite stable-associated signature (MSSAS). The initial signature establishment was performed in GSE39582 (n =454). This was followed by independent validation of this signature in TCGA-CRC (n =312), GSE39084 (n =54), and in-house cohort (n =146). As a result, MSSAS was proven to be an independent risk factor for overall survival (OS) and relapse-free survival (RFS) in non-MSI-H/pMMR CRC. ROC analysis showed that MSSAS had stable and accurate performance in all cohorts for 1, 3, and 5 years, respectively. Further analysis suggested that MSSAS performed better than age, gender, T, N, M, AJCC stage, adjuvant chemotherapy (ACT), tumor mutation burden (TMB), neoantigen, TP53, KRAS, BRAF, and PIK3CA mutation. The clinical validation was executed to further ensure the robustness and clinical feasibility of this signature. In conclusion, MSSAS might be a robust and promising biomarker for advancing clinical management of non-MSI-H/pMMR CRC.